There is a Chance: Songwriting for Hope as Critical Qualitative Research. Issue 2 (August 2021) - Carless, David
How to sustain hope amidst loss during repressive times? It may not be enough to voice the words "there is a chance". But can the act of writing a song, of singing that song, of making a noise, constitute a commitment towards ensuring that there is a chance?